Pelatihan Pengolahan Jamur Tiram untuk Meningkatkan Keterampilan dan Pendapatan Petani Jamur di Desa Tanjung Sangalang - Adventus Panda; Made Dirgantara; Agus Haryono (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Sangalang Hapakat Oyster Mushroom Farmers Group is a farmer group specializes in developing oyster mushrooms in Tanjung Sangalang Village, Central Kahayan District, Katingan Regency, Central Kalimantan Province. This farmer group has nine members, which currently sell seeds, baglogs, and oyster mushrooms to the community. To diversify oyster mushroom products and the knowledge of the group is still needed for oyster mushroom post-harvest processing training. Therefore, this service aims to provide training in oyster mushroom processing in product diversification to maximize the benefits obtained. The activity is divided into two stages: processing oyster mushrooms and online marketing of oyster mushroom products. The processing of oyster mushrooms into commercial food products has been successfully carried out at the Sangalang Hapakat Oyster Mushroom Farmers Group, Tanjung Sangalang Village. All farmer groups, especially mothers, can process oyster mushrooms into home food or commercial use. The products produced from this training are crispy mushrooms, mushroom satay, risoles, and shredded mushrooms. Besides, online marketing training provides knowledge to farmer groups in selling their products on various online market platforms and social media. The village's condition, which still has difficulties with internet access, has made the results of this online marketing training less optimal; however, the farmer groups have been able to market their mushroom products online.